Out-of-plane crashworthiness of bio-inspired self-similar regular hierarchical honeycombs. (1st June 2016) - Zhang, Yong; Lu, Minghao; Wang, Chun H.; Sun, Guangyong; Li, Guangyao
Abstract: Hierarchical materials are widely observed in nature, and have been credited with superior mechanical properties and weight efficiency. In the present work, fractal-appearing self-similar regular hexagonal hierarchical honeycombs (HHHs) are constructed by iteratively replacing each three-edge vertex of a base hexagonal network with a smaller regular hexagon up to second order. The cell wall thickness is adjusted so that the two fractal configurations have identical density as the base honeycomb. To investigate the out-of-plane crashworthiness of this new class of hexagonal hierarchical honeycomb concept, finite element modeling is carried out and validated using experiment results. By comparing the results of three traditional corrugated hexagonal honeycombs (0th order HHH) with those pertinent to two novel 1st and 2nd order HHHs, it can be concluded that hierarchical organization of different cells can enhance the material/strength distribution across the network, resulting in improved crush strength and crush force efficiency. In addition, parametric studies are carried out to explore two further strategies to improve out-of-plane crashworthiness by altering the material distribution, namely changing relative cell sizes and cell wall thickness. The results suggest that further improvement can be realized through optimum designs of the fractal geometries.